Estado del arte en aprendizaje organizacional, a partir de las investigaciones realizadas en facultades de psicología, ingeniería industrial y administración de empresas en Bogotá, entre los años 1992 y 2002 (2004)
The purpose of this research was to establish the state of art of organizational learning,from research works done to accomplish university degrees in faculties of psychology,industrial engineering and business administration in Bogota, Colombia, from 1992 to2002. It was utilized a qualitative methodology, specifically, state of art. Two cards:bibliographic and descriptive, were used to collect the information from the analysis unities.Results showed that from 20553 research works done in the mentioned period, only 13had in its title the words organizational learning. The program with the highest number ofworks in organizational learning was industrial engineering with eight, followed by businessadministration with four and finally psychology with one. All the research works wereeither descriptive or monographic and with diverse conceptual approaches. It is probablethat this few research found in organizational learning in Bogota in the decade, would berepresentative of what it may be found in other Latin American cities.